Pengaruh Penggunaan Aplikasi Fizzo Novel Terhadap Kemampuan Menulis Teks Drama pada Siswa Kelas XI SMK Negeri 4 Medan Tahun Ajaran 2022/2023 - Wiranti Roh Dearni Br. Purba; M. Joharis Lubis (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
The aim of this research is to determine the effect of using the fizzo novel application on the writing ability of class XI students at SMK Negeri 4 Medan for the 2022/2023 academic year. The population in this study was all students in class The research method used is a quantitative experimental method. The research instrument is a drama text writing test which is assessed based on content aspects and linguistic aspects of the drama text. The results of the research show that there is an influence of using the fizzo novel application on the ability to write drama texts in class XI students at SMK Negeri 4 Medan. This is proven by hypothesis testing which shows that the value of Tcount > Ttable is 11.6 > 1.71 with a significance level of 5%.